Insights into the diversity of Hormogastridae (Annelida, Oligochaeta) with descriptions of six new species - Marchán, Daniel F.; Fernández, Rosa; Sánchez, Nuria; Sosa, Irene De; Cosín, Darío J. Díaz; Novo, Marta (Zootaxa, 2018)
The earthworm family Hormogastridae is a relatively diverse group in the Western Mediterranean basin. Since 1887, around thirty species have been described and assigned to four genera. However, from 2010 on, molecular, ecological and morphological studies have questioned the validity of those genera. Meanwhile, new species were discovered and assigned to them, pending a formal systematic revision; such a revision has been performed recently by integrating all the existing sources of information. The resulting classification consists of nine genera, including four newly erected ones. This revised systematic background is used in the current work as a base for the description of six new hormogastrid species: Diazcosinia sacrarium Marchán, Fernández, Díaz Cosín & Novo, sp. nov., Boucheona martae Marchán, Fernández & Díaz Cosín, sp. nov., Boucheona rosae Marchán, Díaz Cosín & Novo, sp. nov., Norana emiliae Marchán, Fernández, Díaz Cosín & Novo, sp. nov., Norana xylocerasi Marchán, Fernández, Díaz Cosín & Novo, sp. nov., and Norana beatrizae Marchán, Fernández, Díaz Cosín & Novo, sp. nov. Norana is a new replacement name for the preoccupied Nora Marchán, Fernández, Díaz Cosín & Novo, 2018. Likewise, Xanina is proposed to replace the preoccupied Xana Díaz Cosín, Briones & Trigo, 1989. We provide an overview of the currently known diversity of the different genera, and we further propose common names in several languages for some of the species of Hormogastridae.